Prehospital Nitroglycerin Safety in Inferior ST Elevation Myocardial Infarction. (2nd January 2016) - Robichaud, Laurie; Ross, Dave; Proulx, Marie-Hélène; Légaré, Sébastien; Vacon, Charlene; Xue, Xiaoqing; Segal, Eli
Abstract: Patients with inferior ST elevation myocardial infarction (STEMI), associated with right ventricular infarction, are thought to be at higher risk of developing hypotension when administered nitroglycerin (NTG). However, current basic life support (BLS) protocols do not differentiate location of STEMI prior to NTG administration. We sought to determine if NTG administration is more likely to be associated with hypotension (systolic blood pressure < 90 mmHg) in inferior STEMI compared to non-inferior STEMI. We conducted a retrospective chart review of prehospital patients with chest pain of suspected cardiac origin and computer-interpreted prehospital ECGs indicating "ACUTE MI." We included all local STEMI cases identified as part of our STEMI registry. Univariate analysis was used to compare differences in proportions of hypotension and drop in systolic blood pressure ≥ 30 mmHg after nitroglycerin administration between patients with inferior wall STEMI and those with STEMI in another region (non-inferior). Multiple variable logistic regression analysis was also used to assess the study outcomes while controlling for various factors. Over a 29-month period, we identified 1, 466 STEMI cases. Of those, 821 (56.0%) received NTG. We excluded 16 cases because of missing data. Hypotension occurred post NTG in 38/466 inferior STEMIs and 30/339 non-inferior STEMIs, 8.2% vs. 8.9%, p = 0.73. A drop in systolic blood pressure ≥ 30 mmHg post NTG occurred in 23.4% of inferior STEMIs and 23.9% of non-inferior STEMIs, p = 0.87. Interrater agreement for chart review of the primary outcome was excellent (κ = 0.94). NTG administration to patients with chest pain and inferior STEMI on their computer-interpreted electrocardiogram is not associated with a higher rate of hypotension compared to patients with STEMI in other territories. Computer interpretation of inferior STEMI cannot be used as the sole predictor for patients who may be at higher risk for hypotension following NTG administration.